MENINGKATKAN KINERJA GURU MELALUI IKLIM SEKOLAH DAN PERSEPSI KEPEMIMPINAN KEPALA SEKOLAH - Warto, Solehudin (Perspektif Ilmu Pendidikan, 2012)
School Principal is the most responsible person develping the effectiveness of all school personnel’s performance. Besides, he/she is also expected to be an effective leader who can distribute his authority appropriately, to coordinate the school activities efficently, and to be a motivator who can enable others to improve their performance continously. This research therefore intended to identify the (a) the role of school climate in improving the teachers’ performance, (b) the role of the perception of school principal’s leadership in improving the teachers’ performance, and (c) the role of school climate and the perception of school principal’s leadership simultaniously in improving the teachers’ performance. The research was conducted in the State Madrasah Aliyah 9 in Pondok Bambu, Jakarta as from March through July 2012. The result of the research shows that in the State Madrasah Aliyah 9 in Pondok Bambu, Jakarta, (a) there is a positive effect of school climate for teachers’s performance improvement in the sense that if the school climate improves, the teachers’ performance will also improve or on the contrary; (b) there is a significant effect of the perception of school principal’s leadership to teachers’s performance; and (c) there is a significant effect of school climate and the perception of school principal’s leadership simultaniously to the teachers’ performance improvement.